Gibberellic Acid Reduces Flowering Intensity in Sweet Orange [Citrus sinensis (L.) Osbeck] by Repressing CiFT Gene Expression - Munoz-Fambuena, Natalia; Mesejo, Carlos; González-Mas, María C.; Iglesias, Domingo J.; Primo-Millo, Eduardo; Agustí, Manuel (2017)
In Citrus, gibberellic acid (GA(3)) applied at the floral bud inductive period significantly reduces flowering intensity. This effect is being used to improve the fruit set of parthenocarpic cultivars that tend to flower profusely. However, the molecular mechanisms involved in the process remain unclear. To contribute to the knowledge of this phenomenon, adult trees of 'Salustiana' sweet orange were sprayed at the floral bud inductive period with 40 mg L-1 of GA(3) and the expression pattern of flowering genes was examined up to the onset of bud sprouting. Trees sprayed with paclobutrazol (PBZ, 2,000 mg L-1), a gibberellin biosynthesis inhibitor, were used to confirm the effects, and untreated trees served as control. Bud sprouting, flowering intensity, and developed shoots were evaluated in the spring. GA(3) significantly reduced the number of flowers per 100 nodes by 72% compared to the control, whereas PBZ increased the number by 123%. Data of the expression pattern of flowering genes in leaves of GA(3)-treated trees revealed that this plant growth regulator inhibited flowering by repressing relative expression of the homolog of FLOWERING LOCUS T, CiFT, whereas PBZ increased flowering by boosting its expression. The activity of the homologs TERMINAL FLOWER 1, FLOWERING LOCUS C, SUPPRESSOR OF OVEREXPRESSION OF CONSTANS 1, and APETALA1 was not affected by the treatments. The number of flowers per inflorescence, in both leafy and leafless inflorescences, was not altered by GA(3) but increased with PBZ; the latter paralleled LEAFY relative expression. These results suggest that GA(3) inhibits flowering in Citrus by repressing CiFT expression in leaves.